2018
DOI: 10.1016/j.freeradbiomed.2017.12.031
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between p22phox and Nox4 in the endoplasmic reticulum suggests a unique mechanism of NADPH oxidase complex formation

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 41 publications
2
20
0
Order By: Relevance
“…An important shared feature of NOX1, NOX2, NOX3, and NOX4 is that their activity is dependent on the co-expression of the p22 phox protein [1] , [21] . The nmf333 mouse strain carries a mutation in the p22 phox gene, which leads to the destabilization of the protein with a consequent loss of Nox2 and Nox4 activity [23] , [40] . Testing collagen IV crosslinking in this strain offered us the possibility to study the possible involvement of four different NOX isoforms simultaneously, although the uniquely limited expression pattern of NOX3 made unlikely that this particular isoform contributes to the formation of sulfilimine linkages.…”
Section: Resultsmentioning
confidence: 99%
“…An important shared feature of NOX1, NOX2, NOX3, and NOX4 is that their activity is dependent on the co-expression of the p22 phox protein [1] , [21] . The nmf333 mouse strain carries a mutation in the p22 phox gene, which leads to the destabilization of the protein with a consequent loss of Nox2 and Nox4 activity [23] , [40] . Testing collagen IV crosslinking in this strain offered us the possibility to study the possible involvement of four different NOX isoforms simultaneously, although the uniquely limited expression pattern of NOX3 made unlikely that this particular isoform contributes to the formation of sulfilimine linkages.…”
Section: Resultsmentioning
confidence: 99%
“…p47phox and p67phox) [20,23]. Translocation of p47phox and p67phox from the cytoplasm to the membrane is essential for the activation of NADPH [23]. Western blotting showed that p47phox and p67phox were indeed mainly distributed in the cytoplasm of HT22 cells.…”
Section: Trpc1 Preventes Ogd/r-induced P47phox and P67phox Translocationmentioning
confidence: 99%
“…Nox2-containing NADPH oxidase is a classic multisubunit complex that contains two plasma membrane subunits-Nox2 and p22phox-and three cytosolic subunits-p47phox, p67phox, and Rac1 [21]. In addition to the interaction between Nox2 and p22phox, a recent study showed that Nox4 also interacts with p22phox [23]. On the basis of this finding, we investigated whether TRPC1 affects NADPH complex assembly.…”
Section: Cellular Physiology and Biochemistry Cellular Physiology Andmentioning
confidence: 99%
See 1 more Smart Citation
“…PDI is also involved in H 2 O 2 generation through interconnections with NOX1 and NOX4, which belong to the nicotinamide adenine dinucleotide phosphate (NADPH) oxidase protein family [81, 82]. In addition, NOX4 occurs in the NOX4-p22 phox complex in the ER membrane and is involved in releasing H 2 O 2 in the ER lumen [83]. One more site of ROS generation in the ER is the microsomal monooxygenase (MMO) system.…”
Section: Sources Of Ros Generation and Antioxidant Defense Systemsmentioning
confidence: 99%